THE PARTICIPATION IN EXTRACURRICULAR ACTIVITIES AND SCHOOLCHILDREN’S RELATIONS WITH TEACHERS - Šukys, Saulius (Acta Paedagogica Vilnensia, 2008)
This article presents research data, the aim of which was to find out the relationship of schoolchildren’s participation in extracurricular activities and their trust in teachers and their inter respect. When analysing research data, the nature of extracurricular activities was also considered. The study included 1382 schoolchildren of different ages (sixth – eleventh grades) from various schools in Kaunas district (the main schools, secondary schools and gymnasiums). The results showed that schoolchildren usually choose sport activities, while artistic training activities are less chosen, and technical activities are the rarest. One fifth of schoolchildren attend several extracurricular activities at the same time. One third of schoolchildren do not attend extracurricular activity at all. The analysis of research data has revealed that schoolchildren, who attend extracurricular activity, trust in teachers more. Compared with schoolchildren who do not attend any after school activity, pupils who attend this activity are more inclined to reveal their personal problems to teachers and believe that teachers would listen to them. On the other hand, more than half of respondents, who attend and do not attend any extracurricular activities, named only several teachers to whom they could appeal for help. Research data has shown a tendency that schoolchildren who are engaged in sport activities trust teachers less if compared with those schoolchildren who attend other activities. Though schoolchildren who attend various extracurricular activities notice respect from teachers more, they themselves are not inclined to respect teachers more. While evaluating data according to the nature of extracurricular activities, no such differences were noticed.